Characterization of thermophilic xylanases from Tengchong Qiaoquan hot spring for lignocellulose bioprocessing and prebiotic production - Li, Jian-Ling; Hu, Wei; Chen, Xiao-Qi; Li, Lin-Hua; Phurbu, Dorji; Zheng, Yan-Yan; Zhang, Yi-Wen; Sun, Jing; Yang, Zheng-Feng; Xie, Kai-Qing; Yang, Li-Quan; Yin, Yi-Rui (Frontiers in Microbiology, 2026)
IntroductionXylanases are key catalysts for valorizing lignocellulosic biomass, yet many available enzymes lack sufficient thermal stability and exhibit suboptimal activity on complex substrates. To address these limitations, we combined enrichment culturing with metagenomic analysis to discover and characterize two novel GH10 family xylanases, Tc15-Xyn6 and Tc15-Xyn10, from the Qiaoquan geothermal area in Tengchong, Yunnan Province.MethodsFollowing molecular cloning, heterologous expression, and purification by Ni2+-chelating affinity chromatography, both enzymes were comprehensively profiled.ResultsTc15-Xyn6 displayed optimal activity at 65 °C and pH 6.6 with a half-life of 2 h at 65 °C, while Tc15-Xyn10 exhibited optimal activity at 60 °C and pH 6.0 with a half-life of 1 h at 60 °C. Both enzymes showed broad pH stability at low temperature: after incubation at 4 °C for 12–24 h across pH 4.0–10.0, Tc15-Xyn6 and Tc15-Xyn10 retained more than 60 and 40% of their initial activity, respectively. Both efficiently hydrolyzed xylan in alkali-treated wheat straw, rice straw, and corn stover, as well as xylan from hot water–treated wheat bran, but yielded distinct product profiles: Tc15-Xyn6 primarily produced xylobiose and xylotetraose, whereas Tc15-Xyn10 generated xylotriose as the main product. The resulting xylooligosaccharides significantly promoted the growth of Lactococcus lactis. Kinetic analyses showed Km and Vmax values of 4.675 mg/mL and 125 μmol/min/mg for Tc15-Xyn6, and 9.36 mg/mL and 59.52 μmol/min/mg for Tc15-Xyn10.DiscussionCollectively, Tc15-Xyn6 and Tc15-Xyn10 combine thermophilicity, thermostability, near-neutral pH preference, and strong performance on complex lignocellulosic substrates, supporting their application in feed processing and targeted production of prebiotic xylooligosaccharides from biomass.